2016
DOI: 10.7324/japs.2016.601006
|View full text |Cite
|
Sign up to set email alerts
|

Protective and therapeutic impact of taurine on some biochemical, immunological and histological parameters in diabetic rats

Abstract: Background: Taurine is a non protein amino acid found in most animal tissues. It is a powerful antioxidant which shares in combating the harmful effect of the reactive oxygen species (ROS), associated to many chronic diseases as diabetes mellitus (DM). The disease is characterized by hyperglycemia and metabolic disorders in the body that leads to the release of ROS in the cells. Methods: The present work evaluates the biochemical and immunological role of taurine (500 mg/kg bwt) in ameliorating diabetes harm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The hepatic cell membrane can automatically repair after alcohol withdrawal if the damage is not serious, while taurine accelerates the repair of hepatic cells, decreasing membrane permeability and inhibiting the release of ALT and AST and improve the serum levels bilirubin [29,41]. Moreover, taurine supplementation also could downregulate these granulomatous and fibrogenic mediators in the liver of S. japonicum -infected mice which further confirmed the anti-granulomatous and anti-fibrotic effects of taurine during S. japonicum infection [42].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The hepatic cell membrane can automatically repair after alcohol withdrawal if the damage is not serious, while taurine accelerates the repair of hepatic cells, decreasing membrane permeability and inhibiting the release of ALT and AST and improve the serum levels bilirubin [29,41]. Moreover, taurine supplementation also could downregulate these granulomatous and fibrogenic mediators in the liver of S. japonicum -infected mice which further confirmed the anti-granulomatous and anti-fibrotic effects of taurine during S. japonicum infection [42].…”
Section: Discussionsupporting
confidence: 60%
“…In acute liver disease model in a rat induced by a single administration of CCl 4 , showed that taurine treatment prevented hepatocellular necrosis, lipid peroxidation, mitochondrial abnormalities. Moreover, taurine also inhibits the transformation of HSCs induced by CCl 4 observed by electron microscopy [29]. Taurine significantly decreased hepatic fibrosis and fibrogenesis of isolated hepatic stellate cells, which are converted to myofibroblasts by oxidative stress in cirrhotic liver, through inhibition of transforming growth factor-β expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most of the studies related to taurine supplementation and its effects on diabetic outcomes were conducted in animal models, which showed its effectiveness in improving glycemic markers (e.g., FBS, insulin, hemoglobin A1C, etc.) [26][27][28][29][30]. These beneficial effects have also recently been reported in humans, as Maleki et al showed an improvement in glycemic and lipid markers in 23 Iranian patients with T2D after eight weeks of taurine supplementation [31].…”
Section: Introductionmentioning
confidence: 78%
“…Effects of taurine on the enzymes GPx and GR have been evaluated in both rodent and human studies. Taurine supplementation recovered hepatic GR activity in diabetic rats [114], whereas hepatic GPx levels remained unaltered by taurine supplementation in type I and type II diabetic mice [105]. However, when young adults were orally supplemented with taurine (50 mg/kg for 2 weeks) after performing eccentric exercise, RBC GPx levels were elevated [115].…”
Section: Effect Of Individual Amino Acid Supplementationmentioning
confidence: 99%